Disaster Risk Finance as a Tool for Development : A Summary of Findings from the Disaster Risk Finance Impact Analytics Project - World Bank Group (World Bank, Washington, DC, 2016)
Since 2013 The World Bank Group has partnered with the Global Facility for Disaster Reduction and Recovery and the U.K. Department for International Development to address some of these gaps in evidence and methodologies. The Disaster Risk Finance Impact Analytics Project has made significant contributions to the understanding of how to monitor and evaluate existing or potential investments in disaster risk finance from a development perspective, and to the evidence base for where such investments have development impact.This note summarizes the findings of this project, presenting the key messages of a book, a technical report, and 14 research papers, categorized into four themes.